2013
DOI: 10.9790/4861-0461724
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive New features of high angular momentum rotational states in some rear-earth nuclei

Abstract: Abstract:The results from the variable moment of inertia (VMI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…This result proves that no chemical interactions occur after the addition of ZnO, and hence its only physical interactions between PVA and ZnO are involved. Mansour et al 37 was reported the same findings where there are no chemical interaction between PVA and ZnO. Further, Figure 4b shows the FTIR spectra of PVA/4 wt% ZnO at different KOH concentrations.…”
Section: Resultssupporting
confidence: 56%
“…This result proves that no chemical interactions occur after the addition of ZnO, and hence its only physical interactions between PVA and ZnO are involved. Mansour et al 37 was reported the same findings where there are no chemical interaction between PVA and ZnO. Further, Figure 4b shows the FTIR spectra of PVA/4 wt% ZnO at different KOH concentrations.…”
Section: Resultssupporting
confidence: 56%